A Critical Analysis of Impact on Employment During and After Covid-19 Lockdown on India - Kashni, Tarun; Thakur, Vishal (International Research Journal of Business Studies, 2021)
This article aims to analyze the impact on employment during the covid19 lockdown period and after lockdown in India. The analysis was based on the ministry of labour and employment and National Statistical Office surveys undertaken before the outbreak of the Covid-19 and follow-up surveys on the effects of the pandemic, also undertaken by Centre for Monitoring Indian Economy Pvt. Ltd. and Statista Inc. One of the largest unemployment since the Great Depression has been generated during the Covid-19 pandemic. This seems to be a real threat that during lockdown the crisis will exacerbate poverty and deepen inequality, with long-term consequences. Countries must now do all possible to prevent unemployment from escalating into a social disaster. Investing in the future and succeeding generations by rebuilding a stronger and more sustainable labour market is critical. The Covid-19 epidemic in India has unquestionably had a significant detrimental influence on India’s employment rates.